2012
DOI: 10.1248/bpb.b12-00494
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of the Polysaccharide Isolated from <i>Tarphochlamys affinis</i> (Acanthaceae) against CCl<sub>4</sub>-Induced Hepatic Injury

Abstract: This study was designed to investigate the protective effects of the polysaccharide isolated from Tarphochlamys affinis (PTA) against CCl 4 -induced hepatotoxicity in rats. Liver injury was induced in rats by the administration of CCl 4 twice a week for 2 weeks. During the experiment, the model group received CCl 4 only; the treatment groups received various drugs plus CCl 4 , whereas the normal control group received an equal volume of saline. Compared with the CCl 4 group, PTA significantly decreased the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Voucher specimens (LYQ2014011801) were identified by the Guangxi Academy of Chinese Medicine and Pharmaceutical Science. PTA was isolated from TA by the Department of Pharmacology, Guangxi Medical University (Guangxi, China), and was prepared according to the method described in our previous paper with slight modification [16]. Tarphochlamys affinis (1000 g) was dried and powdered, extracted three times with 10000 mL water for 2 h at 95-100°C.…”
Section: Materials and Chemicalsmentioning
confidence: 99%
See 3 more Smart Citations
“…Voucher specimens (LYQ2014011801) were identified by the Guangxi Academy of Chinese Medicine and Pharmaceutical Science. PTA was isolated from TA by the Department of Pharmacology, Guangxi Medical University (Guangxi, China), and was prepared according to the method described in our previous paper with slight modification [16]. Tarphochlamys affinis (1000 g) was dried and powdered, extracted three times with 10000 mL water for 2 h at 95-100°C.…”
Section: Materials and Chemicalsmentioning
confidence: 99%
“…Tarphochlamys affinis (Acanthaceae) (TA) has a long history of wide use as a Chinese traditional medicine and has been used to treat tumors, jaundice, acute and chronic hepatitis and other disorders [16]. Our previous studies have shown that more than twenty compounds can be isolated from TA and that polysaccharides have been implicated as the main bioactive ingredient of TA [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Distributed mainly in hepatic cells and kupffer cells, iNOS is not expressed normally. While under pathological state of hepatitis and hepatic injury, iNOS's activity increases significantly and its expression enhances (39). In this state, it continually produces massive NO, which can trigger the generation of a series of inflammatory factors (cytokines) and thus increases inflammatory reaction.…”
Section: Inflammation Related Gene and Protein Expression In Liver Timentioning
confidence: 99%